STRUKTUR KOMUNITAS BRYOFAUNA LUMUT EPIFIT PADA ZONA MONTANA DI KAWASAN GUNUNG UNGARAN, SEMARANG, JAWA TENGAH - Lucia Puspita Anggraini; Rully Rahadian; Jafron Wasiq Hidayat (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
Plant moss (bryoflora) is in important in the tropical forest, including Ungaran mount which is significantly play an important role in water balance. Bryofauna can be found in moss attacking on the tree and is often referred as moss epiphytic bryofauna. The objective of the research were to compare the abundance and diversity of moss epiphytic bryofauna in Montana zone at three different altitudes of Ungaran mount. The sampling methods used was square plots. Bryophytes were collected in 10x10 cm plots on tree trunks. The specimens were extracted using Barlese funnel up to seven days at Laboratory of Ecology and Biosistematics, Departement of Biology, Diponegoro University. The results shows there were 5 classes of 15 ordes and 27 sub ordes/families. The highest abundance of moss epiphytic bryofauna was in altitudes 2040 m asl (24.175 individu/m2), while the lowest was in altitude 1355 m asl (10.275 individu/m2). The biggest diversity of moss epiphytic bryofauna was found in altitude 2040 m asl (H’=2,20), while the lowest was in altitude 1355 m asl (H’=2,00). Acarina has the highest abundance in a these three altitudes. Keywords : Community Structure, Epiphytic Bryophytes, Bryofauna, Montana Zone